KEPATUHAN PENYELENGGARA PELAYANAN PUBLIK DALAM PELAKSANAAN REKOMENDASI OMBUDSMAN REPUBLIK INDONESIA TERKAIT TINDAKAN MALADMINISTRASI TAHUN 2019 - Dharmawan, Muhammad Fachry; Marbun, Robinsar (Hukum dan Masyarakat Madani, 2021)
ABSTRACT Public services are the key to running a perfect government in the framework of the obligation to serve its citizens. In practice, we often encounter complicated problems from the start to the end. So that this bureaucratic process becomes long, inefficient, and expensive. A fast and precise process is needed so that the public service process will be better in the future. One of the causes of not optimal public services in Indonesia is due to inadequate supervision of internal government. Finally, supervisory agencies have become important in their existence in Indonesia, both for direct investigation and following up on reports from the public. After conducting an investigation, the Ombudsman of the Republic of Indonesia will issue a recommendation if it is proven that the public service institution has committed maladministration. However, many question whether these recommendations are being followed. Then whether the recommendation is sufficient as a sanction for maladministration is still in question. This certainty is important to ensure that the government’s performance remains prime and fully pro-people. Keywords: Public Services; Bureaucracy; Public Service Supervisory Agency; Maladministration. ABSTRAKPelayanan publik menjadi kunci dari jalannya roda pemerintahan yang sempurna dalam rangka kewajiban melayani warga negaranya. Dalam prakteknya, seringkali ditemui masalah yang berbelit pada proses awal hingga akhir. Sehingga proses birokrasi ini menjadi lama, tidak efisien, dan mahal. Diperlukan suatu proses yang cepat dan tepat agar proses pelayanan publik semakin baik kedepannya. Salah satu penyebab tidak optimalnya pelayanan publik di Indonesia disebabkan oleh pengawasan yang kurang pada internal pemerintahan. Akhirnya, lembaga pengawas menjadi penting keberadaannya di Indonesia, baik untuk investigasi langsung ataupun menindaklanjuti laporan dari masyarakat. Ombudsman Republik Indonesia dalam setelah melakukan investigasi akan mengeluarkan rekomendasi jika terbukti Lembaga pelayanan publik melakukan tindakan maladministrasi. Namun, banyak pertanyaan apakah rekomendasi tersebut dipatuhi. Lalu apakah rekomendasi tersebut sudah cukup sebagai sanksi atas tindakan maladministrasi tersebut juga masih dalam pertanyaan. Kepastian tersebut menjadi penting untuk menjamin kinerja pemerintahan tetap prima dan berpihak pada rakyat sepenuhnya. Kata kunci: Pelayanan Publik; Birokrasi; Lembaga Pengawas Pelayanan Publik; Maladministrasi.